Examination of Urban Transformation Implementation Legislation: Elazığ Example - Elyiğit, Belkıs; Ekinci, Cevdet Emin (My University, 2024)
In this study, it was aimed to examine and reveal the general results of the models applied in urban transformation works in Elazığ province after the 6.8 Mw Sivrice earthquake on January 24, 2020. The population of the research, Elazığ province sample, is Karşıyaka, Cumhuriyet, Abdullahpaşa, Mustafapaşa, Rüstempaşa, Sürsürü, Kızılay and Sivrice Country Gölbaşı Neighborhoods. The study is qualitative research in the form of a field study in terms of revealing the results of urban transformation implementation at the sample points. In this context, observation technique, interview technique, and documentary scanning technique were used in the descriptive analysis. General physical-structural characteristics of buildings in the observation technique; in the interview technique, 100 building owners and users' opinions about the buildings; In the documentary scanning technique, the reflections of literature information in practice are interpreted as a whole. In comparing the literature information, project technical documents obtained from the Ministry of Environment, Urbanization and Climate Change and Elazığ Municipality were used. As a result, the model to be chosen in the urban transformation process is an important parameter in the success of the application and reaching the desired goal. More qualified urban transformation applications will be achieved by reducing the problems that arise in public transformation projects, especially in determining the legislation, and by choosing the appropriate model for comprehensive transformation.
Keywords: Elazığ; Urban Transformation; Urbanization; Legislation; Urban Transformation Models